AN INTEGRATED GEOPHYSICAL APPROACH USING RESISTIVITY AND ELECTROMAGNETIC DATA TO DELINEATE THE EXTENSION OF PENYU BASIN IN PEKAN, PAHANG. - ABDULLAH, ASHLEY AISYAH YOONG (2020)
Pekan, Pahang is constantly being linked to the offshore sedimentary basin of Penyu basin. Most research that were done on the onshore extension hypothesis did not include research work in Pekan. Establishing a link on the sediments and basement rock between both areas is critical in order to prove the extension of the sedimentary basin. Thus, this study aims to delineate the possible onshore extension of Penyu basin in Pekan through the integration of resistivity, electromagnetic and borehole data. Based on the preliminary study done on the free air gravity data, an elongated feature was observed extending from the southwest part of the Penyu basin.